Working together : a personality-centered approach to management - Isachsen, Olaf (Institute for Management Development IrvineUS, 1991)
Proposes a personality-centered approach to management and teamwork. Attempts a brief study of personality types, drawing on the writings of Jung, Kretschmer, Briggs Myers, Spranger and Keirsey. Provides insights on how to identify personality types; and how to manage each type.